PEMBUATAN GAME PLATFORMER “INTERVAL” DENGAN FITUR AUTO JUMPING - Zinpo Subetha; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Interval is a 2D platformer game made using the Unity game engine. The game tells the story of a treasure hunter finding a ruin that no one else has ever explored. Interval has a game mechanic called auto jumping. Auto jumping makes the player can’t control the character jumping ability. The game controls the timing when the character jumps in a certain interval. The time interval is determined by the game. Game testing is done by using the blackbox method, alpha testing and beta testing. The test results show that the game has features that are rarely found in other games, moderate difficulty level, and replayability.